Screening Bioactive Compounds from Allium sativum as HER2 Inhibitors Targeting Breast Cancer by Docking Methods - Kim, Nguyen Bao; Thi Thuy, Nguyen; Hong Minh, Phan; Kim Thu, Dang; Thanh Tung, Bui (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 37 No 1DO - 10.25073/2588-1132/vnumps.4295, 2021)
This study aims to find the bioactive compounds from Allium sativum for inhibiting HER2 enzyme by using molecular docking method. In this study, the protein tyrosine kinase HER2 structure was obtained from Protein Data Bank; bioactive compounds were collected from previous publications on Allium sativum and were retrieved from PubChem database; molecular docking was done by Autodock vina software; Lipinski’s rule of 5 was used to compare compounds with drug-like and non-drug-like properties; and pharmacokinetic parameters of potential compounds were evaluated using the pkCSM tool. As a result, 55 compounds were collected based on previous publications on Allium sativum . The study results show that there were two compounds having HER2 inhibitory activity stronger than the reference compounds including biochanin A and cyanidin 3-malonylglucoside. Lipinski’s rule of five shows that these two compounds had proprietary drug-likeness. ADMET property prediction of these compounds was also analyzed. The study concludes that biochanin A and cyanidin 3-malonylglucoside may be potential natural product compounds for HER2-positive breast cancer treatment. Keywords Allium sativum, tyrosine kinase HER2, breast cancer HER2 positive, in silico , molecular docking. References [1] S. Libson, M. Lippman. A review of clinical aspects of breast cancer. International review of psychiatry (Abingdon, England) 26(1) (2014) 4. [2] D.J. Slamon, G.M. Clark, S.G. Wong, W.J. Levin, A. Ullrich, W.L. McGuire. Human breast cancer: correlation of relapse and survival with amplification of the HER-2/neu oncogene. Science 235(4785) (1987) 177. [3] U. Krishnamurti, J.F. Silverman. HER2 in breast cancer: a review and update. Advances in anatomic pathology 21(2) (2014) 100. [4] E. Tagliabue, A. Balsari, M. Campiglio, S.M. Pupa. HER2 as a target for breast cancer therapy. Expert opinion on biological therapy 10(5) (2010) 711. [5] D. Biswas, S. Nandy, A. Mukherjee, D.K. Pandey, A. Dey. Moringa oleifera Lam. and derived phytochemicals as promising antiviral agents: A review. South African Journal of Botany 129((2020) 272. [6] H. Lillehoj, Y. Liu, S. Calsamiglia, M.E. Fernandez-Miyakawa, F. Chi, R.L. Cravens, et al. Phytochemicals as antibiotic alternatives to promote growth and enhance host health. Veterinary research 49(1) (2018) 76. [7] B. Bozin, N. Dukic, I. Samojlik, R. Igić. Phenolics as antioxidants in garlic, Allium sativum L., Alliaceae. Food Chem 4((2008) 1. [8] P. Nagella, M. Thiruvengadam, A. Ahmad, J.-Y. Yoon, I.-M. Chung. Composition of Polyphenols and Antioxidant Activity of Garlic Bulbs Collected from Different Locations of Korea. Asian Journal of Chemistry 26(3) (2014) 897. [9] A. Shang, S.-Y. Cao, X.-Y. Xu, R.-Y. Gan, G.-Y. Tang, H. Corke, et al. Bioactive Compounds and Biological Functions of Garlic (Allium sativum L.). Foods 8(7) (2019) 246. [10] M. Thomson, M. Ali. Garlic [Allium sativum]: a review of its potential use as an anti-cancer agent. Current cancer drug targets 3(1) (2003) 67. [11] A. Tsubura, Y.C. Lai, M. Kuwata, N. Uehara, K. Yoshizawa. Anticancer effects of garlic and garlic-derived compounds for breast cancer control. Anti-cancer agents in medicinal chemistry 11(3) (2011) 249. [12] A. Amberg. In Silico Methods. In: Drug Discovery and Evaluation: Safety and Pharmacokinetic Assays. (Eds: Vogel HG, Maas J, Hock FJ, Mayer D). Berlin, Heidelberg: Springer Berlin Heidelberg; pp. 1273 (2013). [13] K. Aertgeerts, R. Skene, J. Yano, B.C. Sang, H. Zou, G. Snell, et al. Structural analysis of the mechanism of inhibition and allosteric activation of the kinase domain of HER2 protein. The Journal of biological chemistry 286(21) (2011) 18756. [14] V.M. Beato, F. Orgaz, F. Mansilla, A. Montaño. Changes in Phenolic Compounds in Garlic (Allium sativum L.) Owing to the Cultivar and Location of Growth. Plant Foods for Human Nutrition 66(3) (2011) 218. [15] M. Thomson, M. Ali. Garlic [Allium sativum]: a review of its potential use as an anti-cancer agent. 1568-0096 (Print)). [16] M.I. Alarcón-Flores, R. Romero-González, J.L. Martínez Vidal, A. Garrido Frenich. Determination of Phenolic Compounds in Artichoke, Garlic and Spinach by Ultra-High-Performance Liquid Chromatography Coupled to Tandem Mass Spectrometry. Food Analytical Methods 7(10) (2014) 2095. [17] A.D. Phan, G. Netzel, P. Chhim, M.E. Netzel, Y. Sultanbawa. Phytochemical Characteristics and Antimicrobial Activity of Australian Grown Garlic (Allium Sativum L.) Cultivars. Foods 8(9) (2019). [18] M. Ichikawa, N. Ide, J. Yoshida, H. Yamaguchi, K. Ono. Determination of Seven Organosulfur Compounds in Garlic by High-Performance Liquid Chromatography. Journal of Agricultural and Food Chemistry 54(5) (2006) 1535. [19] M.D. Dufoo-Hurtado, K.G. Zavala-Gutiérrez, C.-M. Cao, L. Cisneros-Zevallos, R.G. Guevara-González, I. Torres-Pacheco, et al. Low-Temperature Conditioning of “Seed” Cloves Enhances the Expression of Phenolic Metabolism Related Genes and Anthocyanin Content in ‘Coreano’ Garlic (Allium sativum) during Plant Development. Journal of Agricultural and Food Chemistry 61(44) (2013) 10439. [20] L. Vlase, M. Parvu, E.A. Parvu, A. Toiu. Chemical Constituents of Three Allium Species from Romania. Molecules 18(1) (2013). [21] G. Diretto, A. Rubio-Moraga, J. Argandoña, P. Castillo, L. Gómez-Gómez, O. Ahrazem. Tissue-Specific Accumulation of Sulfur Compounds and Saponins in Different Parts of Garlic Cloves from Purple and White Ecotypes. Molecules (Basel, Switzerland) 22(8) (2017) 1359. [22] S. Kim, J. Chen, T. Cheng, A. Gindulyte, J. He, S. He, et al. PubChem in 2021: new data content and improved web interfaces. Nucleic Acids Res 49(D1) (2021) D1388. [23] E.F. Pettersen, T.D. Goddard, C.C. Huang, G.S. Couch, D.M. Greenblatt, E.C. Meng, et al. UCSF Chimera--a visualization system for exploratory research and analysis. Journal of computational chemistry 25(13) (2004) 1605. [24] M.D. Hanwell, D.E. Curtis, D.C. Lonie, T. Vandermeersch, E. Zurek, G.R. Hutchison. Avogadro: an advanced semantic chemical editor, visualization, and analysis platform. Journal of cheminformatics 4(1) (2012) 17. [25] G.M. Morris, R. Huey, W. Lindstrom, M.F. Sanner, R.K. Belew, D.S. Goodsell, et al. AutoDock4 and AutoDockTools4: Automated docking with selective receptor flexibility. Journal of computational chemistry 30(16) (2009) 2785. [26] C.A. Lipinski. Lead-and drug-like compounds: the rule-of-five revolution. Drug Discovery Today: Technologies 1(4) (2004) 337. [27] B. Jayaram, T. Singh, G. Mukherjee, A. Mathur, S. Shekhar, V. Shekhar, Eds. Sanjeevini: a freely accessible web-server for target directed lead molecule discovery. Proceedings of the BMC bioinformatics; 2012. Springer (Year). [28] D.E. Pires, T.L. Blundell, D.B. Ascher. pkCSM: predicting small-molecule pharmacokinetic and toxicity properties using graph-based signatures. Journal of medicinal chemistry 58(9) (2015) 4066. [29] A. Lee. Tucatinib: First Approval. Drugs 80(10) (2020) 1033. [30] B. Moy, P. Kirkpatrick, S. Kar, P. Goss. Lapatinib. Nature Reviews Drug Discovery 6(6) (2007) 431. [31] M.G. Cesca, L. Vian, S. Cristóvão-Ferreira, N. Pondé, E. de Azambuja. HER2-positive advanced breast cancer treatment in 2020. 1532-1967 (Electronic)). [32] M. Shah, S. Wedam, J. Cheng, M.H. Fiero, H. Xia, F. Li, et al. FDA Approval Summary: Tucatinib for the Treatment of Patients with Advanced or Metastatic HER2-Positive Breast Cancer. Clinical Cancer Research(2020) clincanres.2701.2020. [33] P. Wu, T.E. Nielsen, M.H. Clausen. FDA-approved small-molecule kinase inhibitors. Trends in Pharmacological Sciences 36(7) (2015) 422. [34] H. Singh, A.J. Walker, L. Amiri-Kordestani, J. Cheng, S. Tang, P. Balcazar, et al. U.S. Food and Drug Administration Approval: Neratinib for the Extended Adjuvant Treatment of Early-Stage HER2-Positive Breast Cancer. Clinical Cancer Research 24(15) (2018) 3486. [35] D.E. Pires, T.L. Blundell, D.B. Ascher. pkCSM: Predicting Small-Molecule Pharmacokinetic and Toxicity Properties Using Graph-Based Signatures. Journal of medicinal chemistry 58(9) (2015) 4066. [36] C. Prakash, A. Kamel, D. Cui, R.D. Whalen, J.J. Miceli, D. Tweedie. Identification of the major human liver cytochrome P450 isoform(s) responsible for the formation of the primary metabolites of ziprasidone and prediction of possible drug interactions. Br J Clin Pharmacol 49 Suppl 1(Suppl 1) (2000) 35S. [37] S.S. Ashtekar, N.M. Bhatia, M.S. Bhatia. Exploration of Leads from Natural Domain Targeting HER2 in Breast Cancer: An In-Silico Approach. International Journal of Peptide Research and Therapeutics 25(2) (2019) 659. [38] R. Kalirajan, A. Pandiselvi, B. Gowramma, P. Balachandran. In-silico Design, ADMET Screening, MM-GBSA Binding Free Energy of Some Novel Isoxazole Substituted 9-Anilinoacridines as HER2 Inhibitors Targeting Breast Cancer. Current drug research reviews 11(2) (2019) 118. [39] A. Sarfraz, M. Javeed, M.A. Shah, G. Hussain, N. Shafiq, I. Sarfraz, et al. Biochanin A: A novel bioactive multifunctional compound from nature. Science of The Total Environment 722((2020) 137907. [40] J.M. Cassady, T.M. Zennie, Y.H. Chae, M.A. Ferin, N.E. Portuondo, W.M. Baird. Use of a mammalian cell culture benzo(a)pyrene metabolism assay for the detection of potential anticarcinogens from natural products: inhibition of metabolism by biochanin A, an isoflavone from Trifolium pratense L. Cancer research 48(22) (1988) 6257. [41] T. Sehm, Z. Fan, R. Weiss, M. Schwarz, T. Engelhorn, N. Hore, et al. The impact of dietary isoflavonoids on malignant brain tumors. Cancer medicine 3(4) (2014) 865. [42] Y.N. Hsu, H.W. Shyu, T.W. Hu, J.P. Yeh, Y.W. Lin, L.Y. Lee, et al. Anti-proliferative activity of biochanin A in human osteosarcoma cells via mitochondrial-involved apoptosis. Food and chemical toxicology : an international journal published for the British Industrial Biological Research Association 112 (2018) 194. [43] Y. Joshi, B. Goyal. ANTHOCYANINS: A LEAD FOR ANTICANCER DRUGS. International Journal of Research in Pharmacy and Chemistry 1 (2011) 1119. [44] C. Hui, Y. Bin, Y. Xiaoping, Y. Long, C. Chunye, M. Mantian, et al. Anticancer Activities of an Anthocyanin-Rich Extract From Black Rice Against Breast Cancer Cells In Vitro and In Vivo. Nutrition and Cancer 62(8) (2010) 1128.